Green Synthesis, Characterization, and Applications of Aluminum Oxide Nanoparticles Using Aqueous Extract of Clove - Mahdi, Waleed Khalid; Flayyih, Aqeel Oudah; Musa, Falih Hassan (Syarif Hidayatullah State Islamic University, 2024)
In this work, γ-Al2O3NPs were successfully biosynthesized, mediated aluminum nitrate nona hydrate Al(NO3)3.9H2O, sodium hydroxide, and aqueous clove extract in alkali media. The γ-Al2O3NPs were characterized by different techniques like Fourier transform infrared spectroscopy (FT-IR), UV-Vis spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), energy–dispersive x-ray spectroscopy, transmission electron microscope (TEM), Energy-dispersive X-ray spectroscopy (EDX), and atomic force microscopy (AFM). The final results indicated the γ-Al2O3NPs nanoparticle size, bonds nature, element phase, crystallinity, morphology, surface image, particle analysis – threshold detection, and the topography parameter. The identified of γ-Al2O3 bands were detected by the FT-IR spectroscopy. The UV-visible spectrum of γ -Al2O3NPs exhibited an absorption band and (energy gap, Eg = 4.91 eV). It was found that the size range of nanoparticles was (28-37) nm and cubic with agglomerated particles. Antimicrobial activity study showed an excellent inhibition activity of γ-Al2O3NPs against Escherichia coli negative (G-), staphylococcus aureus, positive (G+), and Candida albicans fungal. The effectiveness of the adsorption experiment was proven on binary metal ions, such as cobalt, nickel, and copper, by removing them from water using a nanostructured active surface of γ-Al2O3NPs. The efficiencies removal of Co+2, Ni+2, and Cu+2 ions were 93.22%, 87.49%, and 93.17% respectively.